Flashcard Learning Strategy Builds Understanding and Engagement in Islamic Law: Strategi Pembelajaran dengan Kartu Flash Meningkatkan Pemahaman dan Keterlibatan dalam Hukum Islam - Wardah Afifah; Umar Manshur (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education plays a central role in shaping knowledgeable and skilled generations, but traditional lecture-based methods often limit student engagement. Specific Background: In Islamic law (Fiqh) learning, students frequently face difficulties understanding abstract concepts, leading to boredom and low motivation. Knowledge Gap: While flashcards have been widely used in subjects such as vocabulary acquisition, their application in Fiqh learning, especially to enhance both understanding and engagement, remains underexplored. Aims: This study aims to investigate the effectiveness of flashcard learning media in improving cognitive understanding and active participation of Grade VII students in Fiqh at MTs Nurul Jadid Paiton and MTs Darul Falah Cermee. Results: Using a qualitative descriptive approach through observation, interviews, and documentation, the findings reveal that flashcards significantly enhance student activeness, motivation, and comprehension of Fiqh concepts, particularly in recalling and applying abstract terms. Novelty: Unlike prior studies that focused only on cognitive gains, this research highlights the dual impact of flashcards on both understanding and engagement, tested across two institutions with different contexts. Implications: The study suggests that flashcards are not merely supplementary tools but a transformative strategy for making Fiqh learning more interactive, participative, and effective, offering a model applicable to other abstract-oriented subjects.Highlight : Flashcards help simplify abstract fiqh material. The strategy increases student activeness and motivation. Participation with flashcards improves comprehension and memory. Keywords : Flash Card Learning Media, Student Understanding, Student Engagement, Fiqh Learning, Islamic Law